Selective effects of whey protein concentrate on glutathione levels and apoptosis in rats with mammary tumors. (September 2017) - Cheng, Shih-Hsuan; Tseng, Yang-Ming; Wu, Szu-Hsien; Tsai, Shih-Meng; Tsai, Li-Yu
Abstract: Glutathione (GSH) plays an important role in antioxidant defense and regulation of apoptosis. GSH deficiency is related to many diseases, including cancer, and increased GSH levels in cancer cells are associated with chemotherapy resistance because of resistance to apoptosis. In this study, we investigated the effects of whey protein concentrate (WPC), a precursor of GSH, in rats with mammary tumors induced by treatment with 7, 12-dimethylbenz( a )anthracene (DMBA). DMBA treatment results in cellular changes that mimic the initiation and promotion of carcinogenesis of breast tissue. We aimed to examine the possible preventive effects of diets containing whey protein on DMBA-induced mammary tumors in rats. The results indicate that WPC (0.334 g/kg) supplementation significantly increased the liver GSH levels by 92%, and were accompanied by low Bax/Bcl-2 ratio (from 5 to 3) and cleaved caspase-3/procaspase-3 ratio (from 2.4 to 1.2) in DMBA-treated rats. Furthermore, tumor GSH levels were decreased by 47% in WPC-supplemented rats, which resulted in increased Bax/Bcl-2 ratio (from 0.9 to 2) and cleaved caspase-3/procaspase-3 ratio (from 1.1 to 2.7). In conclusion, supplementation with WPC could selectively deplete tumor GSH levels and, therefore, WPC supplementation might be a promising strategy to overcome treatment resistance in cancer therapy. Graphical abstract: Highlights: The possible preventive effects of WPC were evaluated on DMBA-induced mammary tumors in rats. Results indicated that whey protein concentrate had selective effects in different tissues of rats. WPC supplementation elevated the liver GSH levels and protected the cells from apoptosis. A reduced expression of tumor Nrf2, GCLC, and GR mRNA in tumors when rats supplemented with WPC. WPC supplementation depleted the tumor GSH levels accompanied an increase in apoptosis-related protein.